American like me : reflections on life between cultures - Ferrera, America, 1984-; Dumont, E. Cayce, 1975- (Gallery Books, 2018)
"From award-winning actress and political activist America Ferrera comes a vibrant and varied collection of first person accounts from prominent figures about the experience of growing up between cultures. America Ferrera has always felt wholly American, and yet, her identity is inextricably linked to her parents' homeland and Honduran culture. Speaking Spanish at home, having Saturday-morning-salsa-dance-parties in the kitchen, and eating tamales alongside apple pie at Christmas never seemed at odds with her American identity. Still, she yearned to see that identity reflected in the larger American narrative. Now, in American Like Me, America invites thirty-one of her friends, peers, and heroes to share their stories about life between cultures. We know them as actors, comedians, athletes, politicians, artists, and writers. However, they are also immigrants, children or grandchildren of immigrants, indigenous people, or people who otherwise grew up with deep and personal connections to more than one culture. Each of them struggled to establish a sense of self, find belonging, and feel seen. And they call themselves American enthusiastically, reluctantly, or not at all. Ranging from the heartfelt to the hilarious, their stories shine a light on a quintessentially American experience and will appeal to anyone with a complicated relationship to family, culture, and growing up."--